Exploring Potential: Analysis of Students' Mathematical ProblemSolving Ability on System of Linear Inequalities in Two Variables (SLITV) Material - Loska, Febri; Ayuni, Ayuni; Ainirohmah, Nailu (EDUPEDIA Publisher, 2024)
This research aims to analyze students' mathematical problemsolving abilities in dealing with System of Linear Inequalities in Two Variables (SLITV) material. The research method used is descriptive quantitative with data collection through written tests. The subjects of this research were class XI students at SMAN 2 Tualang, Tualang District, Siak Regency, consisting of 34 students who had studied SLITV material. The technique in this research is tests. The test contains 4 questions with easy, medium and difficult levels. Based on the results of the analysis, it shows that in question number 1, with indicators of the ability to identify elements that are known, asked about, and the adequacy of the required elements, a very good category was obtained with a cumulative percentage of 88.3%. In question number 2 with the indicator of being able to create or compile mathematical models, the category was quite good with a cumulative percentage of 58.3%. In question number 3 with the indicator of choosing and developing a problemsolving strategy, a bad category was obtained with a cumulative percentage of 5.8%. In question number 4 with the indicator of being able to explain and check the correctness of the answers obtained, students received a fairly good category with a cumulative percentage of 53.0%. This means that mathematical problemsolving abilities are good but also need to be developed further in order to achieve maximum mathematical understanding abilities, so that students better understand the basic concepts of the previous material used to solve the problems that have been given.